Bernardo Vega y Emilio Cordero Michel (eds.). Asuntos dominicanos en archivos ingleses. Santo Domingo, Fundación Cultural Dominicana, 1993. 208 p - Cassá, Roberto (Universidad Autónoma de Santo Domingo (UASD), 1993)
No precisa de un resumen.